Treatment of visual axis opacification and secondary membranes with Nd:YAG laser after pediatric cataract surgery under intranasal sedation - Chang, Pingjun; Li, Siyan; Wang, Dandan; Chen, Chaoqiao; Fu, Yana; Hu, Man; Qian, Shuyi; Zhao, Yun-e (Frontiers in Pediatrics, 2023)
Purpose To describe neodymium-doped yttrium-aluminum-garnet (Nd:YAG) laser treatment of visual axis opacification and secondary membranes in pediatric patients with cataracts under intranasal dexmedetomidine sedation. Methods Twenty eyes of 17 patients with secondary membrane formation after cataract extraction were enrolled in this study. Intranasal dexmedetomidine sedation (3 ug/kg) was administered, and Nd:YAG laser (Ellex Super Q, Adelaide, Australia) procedures were performed with children in the sitting position with their chin supported on a laser delivery slit lamp. Preoperative and postoperative visual acuities were documented, and medical records were reviewed. Results The age of the patients ranged from 5 to 83 months (31.82 ± 27.73). Nineteen (95.0%) eyes had congenital cataracts and one (5.0%) had a traumatic cataract. Nd:YAG laser treatment of VAO with ten (50.0%) eyes, pupillary membranes with three (15.0%) eyes, pupillary cortical proliferation with six (30.0%) eyes, and anterior capsule contraction with one (5.0%) eye. Five (25.0%) eyes demonstrated visual acuity improvement, whereas six (30.0%) eyes remained unchanged after laser treatment. The recurrence rate was 30.0% and four eyes underwent a second Nd:YAG membranectomy. No side effects or tolerances due to sedative drugs were observed. Conclusion Nd:YAG laser membranectomy under intranasal dexmedetomidine sedation was safely performed in children as young as 5 months old in a sitting position. This approach facilitates patient convenience, doctor proficiency, and cost reductions. Patients with recurrence can be treated by repeating the procedure.